Помогите!!Упростить (a+b)**-(a-b)** (m+4)**-4(m+1)** 3(2-y)**+4(y-5)** 5(3-5x)**-5(3x-7)(3x+7) **-во второй степени

1

Ответы и объяснения

2013-02-07T13:55:48+00:00

1.(a+b)^2-(a-b)^2=a^2+2ab+b^2-(a^2-2ab+b^2)=a^2+2ab+b^2-a^2+2ab-b^2=4ab

2.(m+4)^2-4(m+1)^2=m^2+8m+16-4(m^2+2m+1)=m^2+8m+16-4m^2-8m-4=12-3m^2

3.3(2-y)^2+4(y-5)^2=3(4-4y+y^2)+4(y^2-10y+25)=12-12y+3y^2+4y^2-40y+100=7y^2-52y+112

4.5(3-5x)^2-5(3x-7)(3x+7)=5(9-30x+25x^2)-5(9x^2-49)=45-150x+125x^2-45x^2+245=80x^2-150x+290

^2-во второй степени